Aminated tung oil-based polyvinyl alcohol, preparation method and application of aminated tung oil-based polyvinyl alcohol in PBAT

By preparing aminated tung oil-based polyvinyl alcohol and mixing it with PBAT, the problem of thermal processing difficulties of PVA is solved, the mechanical properties and compatibility of composite materials are significantly improved, and the application field is expanded.

CN119529457AActive Publication Date: 2025-02-28HEFEI UNIV OF TECH
View PDF 8 Cites 0 Cited by

Patent Information

Application Number
CN202510093745.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-01-21
Publication Date
2025-02-28
Estimated Expiration
2045-01-21

AI Technical Summary

Technical Problem

The high crystallinity and melting point of polyvinyl alcohol (PVA) make it difficult to process hot, limiting its development in the application field.

Method used

Aminated tung oil-based polyvinyl alcohol was prepared by alcoholylation and amination reaction, and mixed uniformly with polybutylene terephthalate-adipate (PBAT) to prepare composite material by melt extrusion.

Benefits of technology

It enhances the mechanical properties of composite materials, improves the plasticity and compatibility of polyvinyl alcohol, and expands its scope of use in application fields.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119529457A_ABST
    Figure CN119529457A_ABST
Patent Text Reader

Abstract

The invention discloses aminated tung oil-based polyvinyl alcohol, a preparation method and application of the aminated tung oil-based polyvinyl alcohol in PBAT (poly (butyleneadipate-co-terephthalate)), and the preparation method of a composite material comprises the following steps: performing alcoholysis on tung oil by using ethanol, and then adding diethylenetriamine to perform amination on the alcoholysis tung oil under the action of a catalyst cobalt (II) terephthalate to obtain aminated tung oil; uniformly mixing the aminated tung oil with polyvinyl alcohol, and reacting to obtain an aminated tung oil plasticized polyvinyl alcohol material; and mixing the plasticized polyvinyl alcohol material with PBAT, and carrying out melt extrusion to obtain the tung oil-based polyvinyl alcohol / PBAT composite material. According to the invention, aminated tung oil is utilized to plasticize polyvinyl alcohol, and by means of chemical grafting and physical hydrogen bonds, tung oil macromolecules can inhibit outward migration of a plasticizer, so that the internal plasticizing performance of polyvinyl alcohol is maintained. The aminated tung oil-based polyvinyl alcohol can also generate stable chemical bonds with PBAT, so that the compatibility of the aminated tung oil-based polyvinyl alcohol and PBAT is improved, and the mechanical effect of the composite material is improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of polyvinyl alcohol composite materials, and in particular to aminated tung oil-based polyvinyl alcohol, a preparation method and application thereof in PBAT. Background Art

[0002] Polyvinyl alcohol (PVA) is a white, stable, non-toxic polymer in the form of powder, flake or flocculent solid. It has good biodegradability, water solubility and barrier properties. Therefore, PVA is regarded as an environmentally friendly polymer material, which is of great significance to replace conventional petrochemical-derived polymers. However, there are strong intermolecular and intramolecular hydrogen bonds between PVA, and the structural regularity of the -OH groups on the PVA main chain is very high, resulting in high crystallinity and melting point, close to or above its decomposition temperature. Therefore, the thermal processing of PVA is very difficult and is the main challenge in the production of PVA products. There are two main strategies to choose from for the treatment of PVA. One major solution is to introduce additional side groups or incorporate comonomers through new polymerization techniques to destroy the chain regularity and hydrogen bond network. Another strategy is to add plasticizers to form hydrogen bonds with the hydroxyl groups of PVA, which can effectively reduce the inherent intermolecular and intramolecular hydrogen bonds of PVA, thereby achieving thermal processing of PVA. Polybutylene terephthalate-adipate (PBAT) is a thermoplastic biodegradable plastic with good ductility and elongation at break, but its low crystallinity, poor rheological properties and low melt strength limit its development in application areas. It is expected that the mixed use of PVA and PBAT will improve the performance of composite materials, expand the scope of use and expand the market size.

[0003] The introduction of plasticizers will reduce the molecular interactions between PVAs, causing the crystallinity and melting point of PVA to decrease, thereby expanding the processing window and making it easier to achieve the melt processing capability of PVA. For example, glycerol is often used as a traditional plasticizer for PVA plasticization because it contains hydroxyl groups in polyols. But its disadvantage is that it is easy to precipitate, migrate and oil. For another example, plasticizers such as plasticized starch, polylactic acid, polyvinyl alcohol and phthalates are added to improve the overall effect of the blending system. For the plasticization of polyvinyl alcohol materials, it is changed by physical hydrogen bonds, and the plasticizing effect is not obvious. In addition, degradable plastics such as PBAT, PVA and polylactic acid are directly melt-extruded to obtain recycled plastic particles, but they have defects in compatibility and little improvement in mechanical properties. Summary of the invention

[0004] Based on the technical problems existing in the background technology, the present invention proposes aminated tung oil-based polyvinyl alcohol, a preparation method and its application in PBAT, thereby enhancing the performance of the composite material.

[0005] The preparation method of the aminated tung oil-based polyvinyl alcohol proposed in the present invention comprises the following steps: S1: Tung oil and anhydrous ethanol undergo alcoholysis reaction under the action of a catalyst to obtain tung oil ethyl ester; S2: Tung oil ethyl ester and diethylenetriamine undergo amination reaction to obtain aminated tung oil; S3: The aminated tung oil and polyvinyl alcohol are mixed and kneaded, and extruded into granules to obtain aminated tung oil-based polyvinyl alcohol.

[0006] Preferably, the catalyst is cobalt(II) terephthalate.

[0007] Preferably, the mass ratio of tung oil, anhydrous ethanol and catalyst is 2-5:1:0.001-0.003; the alcoholysis reaction temperature is 40-55°C, and the time is 4-6h.

[0008] Preferably, the mass ratio of tung oil ethyl ester, diethylenetriamine and anhydrous ethanol is 1:3-6:8-9; the amination reaction temperature is 65-80° C., and the reaction time is 6-8 hours.

[0009] Preferably, the mass ratio of aminated tung oil to polyvinyl alcohol is 0.10-0.40:1; the banburying temperature is 175-185° C., the time is 6-10 min, and the rotation speed is 40-60 r / min.

[0010] The aminated tung oil-based polyvinyl alcohol provided by the present invention is prepared by adopting the above-mentioned preparation method.

[0011] The present invention proposes the use of the above-mentioned aminated tung oil-based polyvinyl alcohol in PBAT.

[0012] The preparation method of the PBAT composite material proposed in the present invention comprises the following steps: uniformly mixing polybutylene terephthalate-adipate and the above-mentioned aminated tung oil-based polyvinyl alcohol, and melt-extruding to obtain a composite material.

[0013] Preferably, the mass ratio of aminated tung oil-based polyvinyl alcohol to polybutylene terephthalate-adipate is 1:1-4; the mixing temperature is 40-55° C., and the mixing time is 1-2 h.

[0014] Preferably, the melt extrusion conditions are: screw speed is 100-130 rpm, feeding rate is 5-7 Hz, and extrusion temperature zones are set to 165, 170, 170, 175, 180, 180, 175, 170°C.

[0015] Beneficial technical effects of the present invention: In the present invention, aminated tung oil is used as a plasticizer for polyvinyl alcohol, and the tung oil-based macromolecules inhibit migration and maintain the plasticized properties of the polyvinyl alcohol material. The amine groups in the aminated tung oil can react with the hydroxyl groups of the polyvinyl alcohol to form chemical bonds, and the internal and external structures of the polyvinyl alcohol molecules are destroyed, weakening the intermolecular forces, making it easier to move, thereby increasing the plasticity of the polyvinyl alcohol.

[0016] In the present invention, the aminated tung oil-based polyvinyl alcohol after plasticization treatment has C=O and -NH structures, which can form more stable hydrogen bonds with -OH in polyvinyl alcohol, so that the hydrogen bond network inside the polyvinyl alcohol material is disconnected, and the plasticizing effect is improved under the dual effects of chemical grafting and physical hydrogen bonding.

[0017] In the present invention, the blending and modification of plasticized polyvinyl alcohol and polybutylene terephthalate-adipate has the characteristics of simple process. The plasticized polyvinyl alcohol can form chemical bonds with the terminal hydroxyl groups of polybutylene terephthalate-adipate, the compatibility of the two materials is improved, and the mechanical properties of the composite material are enhanced. BRIEF DESCRIPTION OF THE DRAWINGS

[0018] Figure 1 The infrared spectra of ATOEE-1, PVA, ATOEE-PVA-1 and ATOEE-PVA / PBAT-1 samples in Example 1 of the present invention; Figure 2 Schematic diagram of the ATOEE-PVA / PBAT synthesis mechanism proposed in the present invention. DETAILED DESCRIPTION

[0019] The present invention will be further explained below in conjunction with specific embodiments.

[0020] Example 1 Weigh 2kg of tung oil (TO) and 1kg of anhydrous ethanol (EtOH), mix and stir, add 1g of cobalt terephthalate as a catalyst, react at 45°C for 4h to obtain tung oil ethyl ester (TOEE). Dissolve 1kg of TOEE and 3kg of diethylenetriamine (DETA) in 8kg of EtOH, react at 80°C for 6h to obtain aminated tung oil, recorded as ATOEE-1. Mix the above 0.2kg of ATOEE-1 and 1kg of PVA, mix at 185°C for 8min, and extrusion granulate at a speed of 40r / min to obtain aminated tung oil-based polyvinyl alcohol material, recorded as ATOEE-PVA-1.

[0021] 1 kg ATOEE-PVA-1 and 2 kg polybutylene terephthalate-adipate (PBAT) were weighed and mixed at high speed for 1 hour to obtain a masterbatch; the masterbatch was melt-extruded, the screw speed was 120 rpm, the feeding rate was 6 Hz, and the extrusion temperature zones were set to 165, 170, 170, 175, 180, 180, 175, 170°C to obtain a composite material, recorded as ATOEE-PVA / PBAT-1.

[0022] Example 2 Weigh 2kg TO and 1kg EtOH, mix and stir, add 1g cobalt (II) terephthalate as a catalyst, react at 45°C for 4h to obtain TOEE. Dissolve 1kg TOEE and 5kg DETA in 8kg EtOH, react at 80°C for 6h to obtain aminated tung oil, recorded as ATOEE-2. Mix the above 0.2kg ATOEE-2 and 1kg PVA, mix at 185°C for 8min, extrusion granulation at 40r / min to obtain aminated tung oil-based polyvinyl alcohol material, recorded as ATOEE-PVA-2.

[0023] S2: Weigh 1 kg ATOEE-PVA-2 and 2 kg PBAT, mix at high speed for 1 hour to obtain a masterbatch; melt-extrude the masterbatch, the screw speed is 120 rpm, the feeding rate is 6 Hz, and the extrusion temperature zones are set to 165, 170, 170, 175, 180, 180, 175, 170°C to obtain a composite material, recorded as ATOEE-PVA / PBAT-2.

[0024] Example 3 1 kg ATOEE-PVA-1 and 1 kg PBAT were weighed and mixed at high speed for 1 hour to obtain a masterbatch; the masterbatch was melt-extruded, the screw speed was 120 rpm, the feeding rate was 6 Hz, and the extrusion temperature zones were set to 165, 170, 170, 175, 180, 180, 175, 170 ° C to obtain a composite material, recorded as ATOEE-PVA / PBAT-3.

[0025] Comparative Example 1 1 kg of PVA and 2 kg of PBAT were weighed and mixed at high speed for 1 hour to obtain a masterbatch; the masterbatch was melt-extruded, the screw speed was 120 rpm, the feeding rate was 6 Hz, and the extrusion temperature zones were set to 165, 170, 170, 175, 180, 180, 175, 170 ° C to obtain a composite material, recorded as PVA / PBAT-1.

[0026] Comparative Example 2 0.2 kg TO, 1 kg PVA and 2 kg PBAT were weighed and mixed at high speed for 1 hour to obtain a masterbatch; the masterbatch was melt-extruded, the screw speed was 120 rpm, the feeding rate was 6 Hz, and the extrusion temperature zones were set to 165, 170, 170, 175, 180, 180, 175, 170 ° C to obtain a composite material, recorded as PVA / PBAT-2.

[0027] Comparative Example 3 Weigh 2kg TO and 1kg EtOH, mix and stir, add 1g cobalt (II) terephthalate as catalyst, react at 45°C for 4h to obtain TOEE. Dissolve 1kg TOEE and 3kg DETA in 8kg EtOH, react at 80°C for 6h to obtain ATOEE. Mix the above 0.4kg ATOEE and 1kg PVA, knead at 185°C for 8min, extrusion granulation at 40r / min to obtain ATOEE-PVA-3.

[0028] 1 kg ATOEE-PVA-3 and 2 kg PBAT were weighed and mixed at high speed for 1 h to obtain a masterbatch; the S1 masterbatch was melt-extruded, the screw speed was 120 rpm, the feeding rate was 6 Hz, and the extrusion temperature zones were set to 165, 170, 170, 175, 180, 180, 175, 170 ° C to obtain a composite material, recorded as ATOEE-PVA / PBAT-4.

[0029] The present invention performs mechanical property tests on the samples prepared in Examples 1-3 and Comparative Examples 1-3, and the results are shown in Table 1. The standard for the tensile strength and elongation at break tests is GB / T1040.1-2018 "Plastics - Determination of tensile properties"; the standard for the flexural strength and flexural modulus tests is GB / T9341-2008 "Plastics - Determination of flexural properties".

[0030] Table 1 Mechanical properties of samples

[0031] As shown in Table 1, the sample prepared in Example 1 has the best mechanical properties, with a tensile strength of 32.18Mpa, an elongation at break of 620%, a flexural strength of 22.67Mpa, and a flexural modulus of 2.35GPa. From Comparative Examples 1 and 2, the mechanical properties of the composite material obtained by directly mixing PVA and PBAT or directly adding TO are not outstanding. By comparing Example 1 with Comparative Example 3, it is proved that the greater the amount of ATOEE added, the better mechanical properties will be achieved, and the appropriate proportion conditions still need to be met. In the embodiment, the tensile strength of the composite material obtained by mixing and melt-extruding PVA and PBAT after plasticization treatment increased by 71.28% at most, and the flexural strength increased by 46.73% at most. This is because the aminated tung oil chemically grafted the hydroxyl groups inside the PVA molecule, reduced the hydroxyl groups, weakened the strong intermolecular and intramolecular hydrogen bonding, and promoted its processability. The plasticized ATOEE-PVA can also be connected to PBAT by chemical bonds, which improves the compatibility of the two materials, and thus shows a more obvious improvement effect in terms of mechanics.

[0032] The present invention performs infrared detection and analysis on the ATOEE-1, PVA, ATOEE-PVA-1 and ATOEE-PVA / PBAT-1 samples in Example 1, and the results are as follows: Figure 1 As shown in the figure, the 1732cm -1 The absorption peak that appears is the C=O contraction vibration. -1 and 3469cm -1 The -NH peak appears at 1634 cm -1 The absorption peak at 1025 cm represents the swing vibration of NH. -1 The absorption peak at 622cm -1 The peak at 3311 cm-1 is attributed to the distortion vibration of NH, indicating the formation of ATOEE. -1 The -OH stretching vibration absorption peak at 2921cm -1 The stretching vibration absorption peak of -CH2 at 1086cm -1 The stretching vibration absorption peak of COC at 1732cm in the spectrum of ATOEE-PVA shows that ATOEE has been successfully introduced into PVA material. -1 The absorption peak becomes sharp and strong, indicating that the aminated tung oil-based PVA reacts with the terminal hydroxyl groups of PBAT to produce ester groups, and PBAT and ATOEE-PVA materials are chemically linked.

[0033] Figure 2Schematic diagram of the preparation mechanism of the ATOEE-PVA / PBAT composite material proposed in the present invention. Figure 2 As shown, firstly, step ① is performed to alcoholize tung oil with anhydrous ethanol to form a larger TOEE molecule; then step ② is performed to aminate the obtained TOEE, and the divalent cobalt ions in cobalt (II) terephthalate can serve as the catalyst active center to effectively activate the amine group of DETA, catalyzing the reaction of the amine group with the TOEE ester group to obtain aminated tung oil, namely ATOEE. In the next step, in step ③, PVA polymer is added, and ATOEE and PVA are mixed by banburying. The -NH2 of the aminated tung oil can be chemically grafted with the -OH of PVA to form a stable chemical bond connection, destroying the hydrogen bond structure of PVA, and plasticizing the PVA material to obtain ATOEE-PVA. Finally, in step ④, the above-mentioned aminated tung oil-based PVA and PBAT are melt extruded under the conditions of melt extrusion, and the carboxyl bond of the plasticized PVA can be connected with the terminal hydroxyl chemical bond of PBAT to form a well-compatible ATOEE-PVA / PBAT composite material.

[0034] Although the embodiments of the present application have been shown and described, it will be understood by those skilled in the art that various changes, modifications, substitutions and variations may be made to the embodiments without departing from the principles and spirit of the present application. The scope of the present application is defined by the appended claims and their equivalents, and all shall be included in the scope of protection of the present application.

Claims

1. A method for preparing aminated tung oil-based polyvinyl alcohol, characterized in that: The steps are as follows: S1: Tung oil and anhydrous ethanol undergo alcoholysis reaction under the action of a catalyst to obtain tung oil ethyl ester; S2: Tung oil ethyl ester and diethylenetriamine undergo amination reaction to obtain aminated tung oil; S3: The aminated tung oil and polyvinyl alcohol are mixed and kneaded, and extruded and granulated to obtain aminated tung oil-based polyvinyl alcohol.

2. The method for preparing aminated tung oil-based polyvinyl alcohol according to claim 1, characterized in that: The catalyst is cobalt(II) terephthalate.

3. The method for preparing aminated tung oil-based polyvinyl alcohol according to claim 1, characterized in that: The mass ratio of tung oil, anhydrous ethanol and catalyst is 2-5:1:0.001-0.003; the alcoholysis reaction temperature is 40-55°C, and the time is 4-6h.

4. The method for preparing aminated tung oil-based polyvinyl alcohol according to claim 1, characterized in that: The mass ratio of tung oil ethyl ester, diethylenetriamine and anhydrous ethanol is 1:3-6:8-9; the amination reaction temperature is 65-80°C and the time is 6-8h.

5. The method for preparing aminated tung oil-based polyvinyl alcohol according to claim 1, characterized in that: The mass ratio of aminated tung oil to polyvinyl alcohol is 0.10-0.40:1; the banburying temperature is 175-185°C, the time is 6-10min, and the speed is 40-60r / min.

6. An aminated tung oil-based polyvinyl alcohol, characterized in that: The method is prepared according to any one of claims 1 to 5.

7. Use of the aminated tung oil-based polyvinyl alcohol as claimed in claim 6 in PBAT.

8. A method for preparing a PBAT composite material, characterized in that: The method comprises the following steps: uniformly mixing polybutylene terephthalate-adipate and the aminated tung oil-based polyvinyl alcohol as claimed in claim 6, and melt-extruding to obtain a composite material.

9. The method for preparing the PBAT composite material according to claim 8, characterized in that: The mass ratio of aminated tung oil-based polyvinyl alcohol to polybutylene terephthalate-adipate is 1:1-4; the mixing temperature is 40-55° C., and the mixing time is 1-2 hours.

10. The method for preparing the PBAT composite material according to claim 8, characterized in that: The melt extrusion conditions were as follows: screw speed of 100-130 rpm, feed rate of 5-7 Hz, and extrusion temperature zones of 165, 170, 170, 175, 180, 180, 175, 170°C.

Citation Information

Patent Citations

  • Tung oil base unsaturated co-ester resin for moulding compound, synthesis method and applications thereof

    CN105418902A

  • Tung oil hyperbranched polyester plasticizer as well as preparation method and application thereof

    CN112521697A

  • Thermoplastic starch / PBAT biodegradable composite material and preparation method thereof

    CN115044070A

  • Tung oil-based plasticizer and preparation method thereof

    CN115677547A

  • Environment-friendly composite material and preparation method thereof

    CN116144147A